Per-oral Pyloromyotomy (POP) for Medically Refractory Gastroparesis: Short Term Results From the First 100 Patients at a High Volume Center. Issue 3 (September 2018) - Rodriguez, John; Strong, Andrew T.; Haskins, Ivy N.; Landreneau, Joshua P.; Allemang, Matthew T.; El-Hayek, Kevin; Villamere, James; Tu, Chao; Cline, Michael S.; Kroh, Matthew; Ponsky, Jeffrey L.
Abstract : Objective: For patients with gastroparesis, temporary pyloric disruption has been shown to improve symptoms and gastric emptying. Per-oral pyloromyotomy (POP) is an innovative endoscopic procedure to divide the pylorus from within a submucosal tunnel, as a corollary to surgical pyloromyotomy. Here we evaluate subjective and objective outcomes 12-weeks after POP at a high volume center. Methods: The first 100 consecutive patients undergoing POP were included, with procedure dates between January 2016 and October 2017. Patients were evaluated using the Gastroparesis Cardinal Symptom Index (GCSI), and 4-hour solid-phase scintigraphic gastric emptying studies (GES) prior to procedure and at 90 days post-POP Results: The study cohort was 85% female with a mean age of 45.0 ± 14.6 years. Gastroparesis etiologies were divided among idiopathic (56%), diabetic (21%), postsurgical (19%), and other in 4%. There were 67% of the patients who had previous endoscopic or surgical interventions for gastroparesis. Most POP procedures were performed in the operating room (97%) and were completed in an average of 33 minutes. Ten patients incurred complications (10%), which included 1 diagnostic laparoscopy and 2 cases of gastrointestinal bleeding. Overall GCSI improved from a preoperative mean of 3.82 ± 0.86 to 2.54 ± 1.2 ( P < 0.001). The improvement in each GCSI subscore was also highly statistically significant. Among the patients with postoperative GES available, 78% had objectively better 4-hour emptying with a mean improvement in retention by 23.6% ( P < 0.001). This included 57% of patients with normal gastric emptying post-POP. Conclusion: For patients with medically refractory gastroparesis, POP results in both subjective and objective improvement in the majority of patients. Prior intervention does not obviate POP as a therapeutic option. POP should be included along the treatment algorithm for patients with gastroparesis as an organ-sparing procedure.